К определению художественного метода Достоевского и его гносеологической наполненности - КОВАЛЕВСКАЯ, ТАТЬЯНА ВЯЧЕСЛАВОВНА (SlavVaria, 2021)
Toward Defining Dostoevsky’s Poetic Method and Its Epistomological Contents. The article offers a new concept of Dostoevsky’s poetic method; the concept is based on the writer’s epistemology and philosophical and religious anthropology. The article problematizes the notion of polyphony as antithetic to Dostoevsky’s system of ideas. In formulating his anti-heroes’ ideas, Dostoevsky frequently alters his own ideas in such a way that they radically change their essence while preserving their outward appearance. This is what we call an apatetic novel. To find their way in the world of apatetic ideas, readers must assess them in the perspective of truth that, in Dostoevsky’s view, has been given to people in the image of Christ in the flesh and consists in loving one’s neighbor as oneself.